2013
DOI: 10.1007/s11356-013-1818-3
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of chemically stabilized arsenic-contaminated soil in a landfill cover

Abstract: The aim of the study was to determine if an As-contaminated soil, stabilized using zerovalent iron (Fe0) and its combination with gypsum waste, coal fly ash, peat, or sewage sludge, could be used as a construction material at the top layer of the landfill cover. A reproduction of 2 m thick protection/vegetation layer of a landfill cover using a column setup was used to determine the ability of the amendments to reduce As solubility and stimulate soil functionality along the soil profile. Soil amendment with Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Main chemical constituents (Table 1) were Fe, Ti and Al oxides, which together accounted for 70% of the total constituents of the RM. The main mineral phases, determined by X-ray powder diffraction, in this RM were haematite (αÀFe 2 …”
Section: Rm Sampling Composition and Initial Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Main chemical constituents (Table 1) were Fe, Ti and Al oxides, which together accounted for 70% of the total constituents of the RM. The main mineral phases, determined by X-ray powder diffraction, in this RM were haematite (αÀFe 2 …”
Section: Rm Sampling Composition and Initial Propertiesmentioning
confidence: 89%
“…Moreover, a large number of old EU landfills should be appropriately closed within the next few years as a consequence of the requirements established by the EU Directive on the Landfill of Waste 99/31/EG [1]. To meet these requirements, more than a billion tonnes of construction materials are needed [2]. Thus, the development of technologies for pollution avoidance and confinement remains a very important social and industrial target for Europe [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, significant correlations have been found between dissolved Fe and As confirming that Fe oxides/hydroxides represent one of the major sorbing agents for As in soils (Masscheleyn et al 1991;Marin et al 1993;Kumpiene et al 2013;Molinari et al 2013). On the other hand, it was found that the speciation of As in the water extracting solution depended on the soil uses.…”
Section: Water-extractable As Concentrationsmentioning
confidence: 90%
“…Peat also has high CEC (94 cmol[+] kg −1 ) and allows efficient immobilization of metal cations from pore water. Peat mixed or modified with Fe‐based materials was effectively used for efficient removal of metalloids (Ansone et al, 2013; Kumpiene et al, 2013). In the present study, the amendment of peat mixed with Fe‐rich sludge decreased up to 85% the total As concentrations in tailings.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, peat mixed or modified with Fe‐based materials was found to be efficient in removing metalloids. The better As removal was explained by the existence of As‐O‐Fe bonds in Fe‐peat amendment (Ansone et al, 2013; Kumpiene et al, 2013; Zhang et al, 2018). It is worth noting that Fe‐based materials were reported to have a high metalloids scavenging capacity (Bolan et al, 2014).…”
mentioning
confidence: 98%